Analysis of the Association Between Polymorphisms within PAI-1 and ACE genes and Ischemic Stroke Outcome After rt-PA Therapy - Dušanović Pjević, Marija; Beslac Bumbaširevic, Ljiljana; Vojvodic, Ljubica; Grk, Milka; Maksimović, Nela; Damnjanović, Tatjana; Novaković, Ivana; Kačar, Katarina; Pesic, Milica; Perovic, Dijana; Savic, Milan; Maksic, Veljko; et al. (Journal of Pharmacy & Pharmaceutical Sciences, 2019)
Purpose: Treatment of Ischemic stroke (IS) in acute phase is based on the use of thrombolytic rt-PA therapy. We aimed to determine whether different alleles and genotypes of I/D ACE gene and 4G/5G PAI-1 gene polymorphisms may influence outcome of rt-PA therapy in patients with IS and the occurrence of haemorrhagic transformation (HT). Methods: Our study included 94 consecutive patients with IS treated with rt-PA. Modified Rankin Scale (mRS) at 3rd month after IS was used to determine the stroke outcome, with scores 0-1 defining the favourable outcome, and scores 2-6 defining poor outcome. Genotypisation of the ACE-1 I/D polymorphism was performed by polymerase chain reaction and of the PAI-1 4G/5G polymorphism by polymerase chain reaction - restriction fragment length analysis. Results: Regarding PAI-I 4G/5G polymorphism, 44 patients (46.8%) were heterozygotes, and the number of 4G/4G and 5G/5G homozygotes was the same – 25 each (26.6%). Number of heterozygotes for the ACE I/D polymorphism was 54 (57.4%), 9 patients (9.6%) had II, and 31 (33%) DD genotypes. A favourable outcome was recorded in 26 (28.0%) and the poor outcome in 67 (72.0%) patients. Favourable and poor outcome groups did not differ significantly in PAI-1 4G/5G and ACE I/D polymorphisms genotype or allele frequencies. There was a statistically significant difference in the occurrence of HT between patients with ACE II and patients with ACE ID or DD genotypes (p=0.035). Conclusion: Results of our study suggest that stroke patients with ACE II genotype, treated with rt-PA, may be at risk of HT.